analisis retorika antarpribadi podcast Deddy bersama Prabowo: kontruksi pesan gaya bicara relasi: analisis konstruksi pesan teori Aristoteles, analisis gaya bicara pendekatan linguistik, analisis relasi teori A DeVito - Mayda Yaffa Elsa; Moh. Syamsul Ma’arif (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
This study aims to conduct an in-depth analysis of message construction, speaking style, and interpersonal relationships formed in an episode of the Deddy Corbuzier Podcast featuring Prabowo Subianto. This qualitative research employs data collection methods including observation, documentation, and systematic note-taking. Data analysis involves processes of data reduction, data presentation, and conclusion drawing. Message construction is analyzed using Aristotle’s Rhetorical framework (Ethos, Pathos, Logos), speaking style is examined through a linguistic approach, and interpersonal relations are analyzed using DeVito’s five dimensions: openness, empathy, supportiveness, positivity, and equality. The findings indicate that the message construction is strategically designed to redefine the public image from rigid to more humanistic. Ethos is established through emotional control, Pathos through humor and personal narratives, and Logos is reinforced by references to real-life experiences. Prabowo’s speaking style demonstrates significant adaptation, shifting toward a more casual language style (using informal pronouns such as “lo-gue”) with a calm intonation. This adjustment functions as a strategic effort to reduce formality and bridge the distance between the speaker and the audience. Interpersonal relations successfully manage differences in social status by creating functional equality across DeVito’s five dimensions. In conclusion, the appearance of a political figure in this podcast provides an opportunity for direct interaction and public image renewal aligned with contemporary digital media trends, as well as for fostering more personal closeness with the public, making this communication process an effective post-election image adaptation strategy.